Optimisation of solid-to-liquid ratio in morinda citrifolia l. Fruits: enhancing yield and total flavonoid content through extraction kinetics with high antioxidant potential - Mohammad Amil Zulhilmi Benjamin; Tun Faiz Al Hakim Tun Faisal Ismail; Mohd Azrie Awang (Institut Kimia Malaysia, 2024)
Morinda citrifolia L., commonly known as 'Noni,' holds substantial potential in food and pharmaceutical research due to its bioactive constituents, which can be extracted using innovative techniques. This study specifically focuses on optimising the solid-to-liquid extraction process of crude extracts to obtain yields and total flavonoid content (TFC) from M. citrifolia fruits at different solid-to-liquid ratios (1:10 g/mL, 1:20 g/mL, and 1:30 g/mL) using ultrasound-assisted extraction in an ultrasonic water bath. The extraction kinetics were examined using six common mathematical models: first-order kinetic, second-order kinetic, second-order rate, Peleg, power law, and two-site kinetic, along with the assessment of goodness-of-fit. Additional evaluation involved measuring antioxidant activity through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The results revealed that at 1:10 and 1:20, the highest yield achieved was 1.46 ± 0.00 mg/mL within 120 min, while the TFC reached 3.57 ± 0.00 mg CE/g db within 110 min, respectively. The two-site kinetic model effectively elucidated the extraction kinetics of both yield and TFC at different ratios, displaying exceptional goodness of fit. For antioxidant activity, the DPPH inhibition results demonstrated significant antioxidant effects, with a peak of 88.39 ± 0.07 % observed at 1:20, compared to the positive control (90.02 ± 0.12 %). Overall, the findings of this study offer valuable insights that contribute to the establishment of standardised extraction methods, cost-effective operations, and time savings for the food and pharmaceutical industries.